The Functions of the Economic Science and Globalization - Kavaliauskienė, Virginija (Ekonomika, 2002)
The article describes the basic functions of economic science under the modern conditions, looks into the effectiveness of performance of this functions and produces the evidence about the unlimited possibilities which gives the science to the humanity in it’s acceleration of evolution under globalization. Globalization is going on objective and unrestraint. It gives necessities for human in the important spheres of activities, such as information, technology and economy. Globalization intensifies the course of the economic process and the polarization of the participants. It changes the proportion of economic and politic forces in the world, quickens the formation of information’s human. All process distinguishes oneself differential unevenness. Globalization can’t solve itself the human problems, but it gives nice technical, information and economic possibilities for the scientific, smooth and successful solving of problems. The article’s author formulates the main modern problems of the economic science and economic practice. 1. Full value of economic subject: Formation, development, collapse, destruction, protection. 2. The balanced economic growth. 3. Economic transformation: Nature: spontaneous, not forced, forced; Mechanism: precautions, catalysts, destabilize; Consequences: foreseen, desirable, not foreseen, pernicious. 4. Non-formal economic development on a global scale: Causes, consequences, prospects. 5. The rightness of distribution and redistribution of social product. Especially sore economic practice problems are forming of a real value economic subject, use the economic law to ruinous direction for society and growth of informal, shadow economic. The substantial change period begins if the corruption increases on a world scale and socialization process of the most persons is disorder and material basis of a scale of value priority is losing. The solving of principal 1, 2, 3 problems profiles the solving of other actual economic problems (4, 5, 6).